Potential efficacy of caffeine ingestion on balance and mobility in patients with multiple sclerosis: Preliminary evidence from a single-arm pilot clinical trial. - Afsoon Dadvar; Melika Jameie; Mehdi Azizmohammad Looha; Mohammadamin Parsaei; Meysam Zeynali Bujani; Mobina Amanollahi; Mahsa Babaei; Alireza Khosravi; Hamed Amirifard (PLoS ONE, 2024)
Objectives Caffeine's potential benefits on multiple sclerosis (MS), as well as on the ambulatory performance of non-MS populations, prompted us to evaluate its potential effects on balance, mobility, and health-related quality of life (HR-QoL) of persons with MS (PwMS). Methods This single-arm pilot clinical trial consisted of a 2-week placebo run-in and a 12-week caffeine treatment (200 mg/day) stage. The changes in outcome measures during the study period (weeks 0, 2, 4, 8, and 12) were evaluated using the Generalized Estimation Equation (GEE). The outcome measures were the 12-item Multiple Sclerosis Walking Scale (MSWS-12) for self-reported ambulatory disability, Berg Balance Scale (BBS) for static and dynamic balance, Timed Up and Go (TUG) for dynamic balance and functional mobility, Multiple Sclerosis Impact Scale (MSIS-29) for patient's perspective on MS-related QoL (MS-QoL), and Patients' Global Impression of Change (PGIC) for subjective assessment of treatment efficacy. GEE was also used to evaluate age and sex effect on the outcome measures over time. (Iranian Registry of Clinical Trials, IRCT2017012332142N1). Results Thirty PwMS were included (age: 38.89 ± 9.85, female: 76.7%). Daily caffeine consumption significantly improved the objective measures of balance and functional mobility (BBS; P-value<0.001, and TUG; P-value = 0.002) at each study time point, and the subjective measure of MS-related QoL (MSIS-29; P-value = 0.005) two weeks after the intervention. Subjective measures of ambulatory disability (MSWS-12) and treatment efficacy (PGIC) did not significantly change. The effect of age and sex on the outcome measures were also assessed; significant sex-time interaction effects were found for MSWS-12 (P-value = 0.001) and PGIC (P-value<0.001). The impact of age on BBS scores increased as time progressed (P-value = 0.006). Conclusions Caffeine may enhance balance, functional mobility, and QoL in PwMS. Being male was associated with a sharper increase in self-reported ambulatory disability over time. The effects of aging on balance get more pronounced over time. Trial registration This study was registered with the Iranian Registry of Clinical Trials (Registration number: IRCT2017012332142N1), a Primary Registry in the WHO Registry Network.